2016
DOI: 10.4172/2252-5211.1000237
|View full text |Cite
|
Sign up to set email alerts
|

Water Absorption and Thickness Swelling Characterization of Chicken Feather Fiber and Extracted Fish Residue Powder Filled Epoxy Based Hybrid Biocomposite

Abstract: Excellent compatibility characteristics of CY-230 epoxy resin with a large variety of fibers and elemental particulates has lead us to develop the cost effective materials with desired characteristics. In the current investigation the livestock waste i.e. Chicken Feather Fiber (CFF) and extracted Fish residue is used as reinforcing materials. Here, the physical appearance, weight density, thickness swelling and water absorption characteristics of the chicken feather fiber filled epoxy based composite is scruti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 4 publications
0
7
0
Order By: Relevance
“…Similarly, Bansal, et al studied the water absorption behavior of CFF reinforced with epoxy composites. The density of the composites is reduced, the void fraction, water absorption, and thickness swelling are marginally increased with the addition of the CFF 20 . In recent work, Reddy, et al showed that the keratin from chicken feather can be used as an effective sizing agent on polyester and polyester/cotton blends 21 .…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Bansal, et al studied the water absorption behavior of CFF reinforced with epoxy composites. The density of the composites is reduced, the void fraction, water absorption, and thickness swelling are marginally increased with the addition of the CFF 20 . In recent work, Reddy, et al showed that the keratin from chicken feather can be used as an effective sizing agent on polyester and polyester/cotton blends 21 .…”
Section: Introductionmentioning
confidence: 99%
“…Increasing the amount of chicken feather led to increasing of open porosity in composites as was proved with SEM images of composite samples. Bansal et al also showed that increasing w% of chicken feather caused water absorption to increase as the voids in epoxy composites were raised (Acda, 2010; Bansal et al, 2016). We can conclude that water absorption values show compliance with swelling thickness and open porosity values, except for the FFB3P series.…”
Section: Resultsmentioning
confidence: 99%
“…Epoxy resin was selected as the matrix due to easy handling and curing at room temperature, toughness, strong adhesion, chemical resistance and other specialized properties and compatibility. Epoxy resin O belongs to the family of thermoset plastics which do not give off reaction products when cured and has low shrinkage (Bansal et al, 2016).…”
Section: Methodsmentioning
confidence: 99%
“…wing to the global environmental concerns (Odetoye et al, 2019), more recent research has been targeted towards green technology and development of eco-friendly materials such as biocomposites (Bansal et al, 2016;Adekomaya & Adama, 2018;Rahman et al, 2019). More so, disposal of agricultural waste into running water leads to the breeding of mosquitoes and environmental pollution, uncontrolled surface run off leading to gully erosion which made some places inhabitable (Ferronato & Torretta, 2019).…”
Section: Introductionmentioning
confidence: 99%